Design of a phased array with a beam scanning functionality based on the arithmetic phase difference. Issue 1 (1st April 2022) - Fan, Haifeng; Zhang, Yiming; Wang, Xuhong; Gao, Junxia
Abstract: The demand for phased array antennas increases not only for the traditional military industry but also in commercial areas such 5G mobile network platforms, Internet of Things (IoT), and satellite communication applications. In this paper, a phased array with beam scanning function is designed based on arithmetic phase difference between array elements. In the design process, the initial complex model is simplified into a simple element model with periodic conditions, which makes the analysis faster and more efficient. Finally, two phased array designs based on microstrip patch antenna are studied, and the simulation results verify the correctness of the design method.